The coal: alternative to the power crisis in Peru - Giraldo Paredez, Emiliano Mauro (2012)
In this article, we carry out an analysis of the energy reserve from coal, taking as a base the mines studied and the work carried out by the Geological Institute of Mining and Metalworking-INGEMMET, as an alternative to solve the energy crisis that Peru is already experiencing. The investigation began as a result of an article published in issue vol. 10 N ° 20 of the magazine of the FIGMMG Research Institute, on coal mining in northern Peru and the result of the study of more than 20 mines according to their classification, location, geology, mining and the prevailing social problem. According to the World Bank and other organizations, our country will continue to grow, therefore there will be greater energy demand, demand that cannot be covered with the scarce existing reserve; to which is added the gradual reduction of the flow of the rivers that operate the hydroelectric plants, due to the increasing thawing of the snow-capped mountains due to global warming, with glaciers being the main sources of water during the dry season in our country. Projecting in the medium and long term, to the phenomenon of global warming will be added the depletion of gas and oil reserves and / or their high cost, scenarios that make one think and think about other energy sources such as coal, considering their abundance in our territory . Therefore, it is worth deepening this study for the installation of coal-fired thermoelectric plants at strategic points, to minimize their cost of transportation and to have cheap electrical energy; also generating sources of work, direct and indirect, and strengthening the decentralization that our country lives.